"Be Therefore Persuaded Ladies": Boston's Gleaning Circle (1805–13). Issue 1 (2nd January 2017) - Fredlund, Katherine
Abstract : While much research has considered women's rhetorical practices in the later part of the nineteenth century, less is known about the practices of women at the beginning of the century. Indeed, the faulty binary of public and private, and the resultant ideological separation of these spaces, has led scholars to devalue such women's rhetorical practices. Yet in 1805 an elite group of young women formed the Boston Gleaning Circle in order to continue their education, and the content of the Circle's archive indicates that deliberative rhetoric was an essential aspect of women's relationships during this time period.